Local adaptation in rotifer populations - Campillo, Sergi; García-Roger, Eduardo M.; Carmona, María José; Serra, Manuel (Evolutionary ecology, 2011)
The adaptation of organisms to their environment has been a subject of study for a long time. One method to study adaptations in populations involves comparing contemporary populations of the same species under different selective regimes, in what is known as a ‘local adaptation’ study. A previous study of the cyclically parthenogenetic rotifer Brachionus plicatilis found high heritabilities for some life-history traits. Some of these life-history traits significantly differed among six populations from Eastern Spain and data suggested some traits to have higher evolutionary rates than neutral genetic markers. Here, by studying the same B. plicatilis populations, we examine the variation and possible local adaptation of their main life-history traits, closely related to fitness, in relation to habitat salinity and temperature. These environmental factors have been shown to play a key role in the ecological differentiation among co-generic species of B. plicatilis . The results obtained in this study show that: (1) the seasonality of rotifer populations from Eastern Spain has profoundly influenced sexual reproduction strategies; (2) salinity is probably a key factor in the ecological specialization of some populations; and (3) rotifer populations harbour high variability in their fitness components.